EMPLOYERS’ SATISFACTION LEVEL TOWARDS GRADUATES WITH OIL AND GAS UNIVERSITY QUALIFICATIONS - Ybyrayeva, Yerkezhan (Nazarbayev University Graduate School of Education, 2022)
The oil and gas industry in Kazakhstan is traditionally considered the leading activity that determines the main trends in the development and growth of the economy in the country and has one of the greatest influence on the welfare of Kazakhstani people. This situation is explained by the presence of large reserves of oil and gas in Kazakhstan, a high level of production of these types of raw materials in the country and the corresponding volumes of exports. Moreover, the oil and gas industry in Kazakhstan, with the highest production profitability among other activities, accumulates most of the foreign direct investment attracted to the country. Compared to the size of the entire economy, namely nominal GDP, the scale of the oil and gas industry in Kazakhstan is also significant. Given the impact this industry has on our economy, it is important to understand that workers must meet all standards to perform well. However, in many countries there is a tendency that employers are not completely satisfied with their employees, namely, graduates of oil and gas university programs. They argue that while the number of graduates is growing, the quality of training and skills acquired does not meet the requirements of the companies. I chose this topic to find out how things are on this issue in Kazakhstan. I wanted to find out to what extent Kazakhstani higher education meets the requirements of employers in order to help readers understand the problems of higher education institutions and to help the Ministry of Education and universities to cooperate with the labor market and to build practices to prepare better employees.
Keywords: oil and gas industry; university-industry collaboration; graduates; employers; Type of access: Gated Access